2003
DOI: 10.1136/thorax.58.6.484
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial comparing nicotine replacement therapy (NRT) plus brief counselling, brief counselling alone, and minimal intervention on smoking cessation in hospital inpatients

Abstract: Background: Guidelines recommend that smoking cessation interventions are offered in all clinical settings to all smokers willing to make a quit attempt. Since the effectiveness of routine provision of behavioural counselling and nicotine replacement therapy (NRT) to smokers admitted to hospital has not been established, a randomised controlled trial of these interventions given together compared with counselling alone or minimal intervention was performed in hospital inpatients. Methods: Medical and surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 23 publications
5
87
1
1
Order By: Relevance
“…Studies have shown that, despite the ban on in-hospital smoking, 25% of patients smoke in the hospital environment, and that, of hospitalized smokers, 55% report withdrawal symptoms, only 6% receive nicotine replacement therapy, 63% relapse in the first week, and 45% relapse on post-discharge day 1. (5)(6)(7)(8) There are few national data on in-hospital smoking and its management. In a study conducted in a general hospital in the city of São Paulo, Brazil, in which the prevalence of active smoking among inpatients was 17%, the authors drew attention to the need to obtain information about smokers admitted to other hospitals in the country, in order to develop protocols for the treatment of such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that, despite the ban on in-hospital smoking, 25% of patients smoke in the hospital environment, and that, of hospitalized smokers, 55% report withdrawal symptoms, only 6% receive nicotine replacement therapy, 63% relapse in the first week, and 45% relapse on post-discharge day 1. (5)(6)(7)(8) There are few national data on in-hospital smoking and its management. In a study conducted in a general hospital in the city of São Paulo, Brazil, in which the prevalence of active smoking among inpatients was 17%, the authors drew attention to the need to obtain information about smokers admitted to other hospitals in the country, in order to develop protocols for the treatment of such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarises the studies included in this review. Of the nine studies, three were conducted the UK, (Andrews et al, 2006;McHugh et al, 2001;Molyneux et al, 2003) three in Australia, (Myles et al, 1996;Myles et al, 2004;Wolfenden et al, 2005) two in Denmark (Moller, et al, 2002;Sorensen, & Jorgensen, Key: CABG = Coronary Artery Bypass Graft surgery; Exp = Experimental Group; Con = Control Group; n.s. = non significant; sig.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Based on the inclusion criteria, 51 full text articles were obtained but following further scrutiny by the reviewers 42 of these were excluded. Nine full text articles were retained in this review (Andrews, Bale, Chu, Crame, & Aveyard, 2006;McHugh et al, 2001;Moller, et al, 2002;Myles et al, 1996;Myles, Leslie, Angliss, Mezzavia, & Lee, 2004;Molyneux et al, 2003;Ratner et al, 2004;Sorensen, & Jorgensen, 2003;Wolfenden et al, 2005). Studies were excluded if the smoking cessation intervention was delivered postsurgery, or they were not genuine RCTs.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations